Impact of Cognitive Biases on Mutual Fund Investors In Delhi & NCR Region - Garg, Girish; Arora, Suneel (International Journal of Psychosocial Rehabilitation, 2020)
The current study, "Impact Of Behavioural Biases On Mutual Fund Investors In Delhi And NCR Region," becomes involved with the functions to consider the degree of mutual fund information through investors in a decided-upon pattern and to bear in mind the effect of cognitive biases in a decided-upon pattern. The cognitive biases included representativeness bias, cognitive dissonance bias, and framing bias, which were taken into consideration. For meeting the purposes, the vital records were comprised of fifty mutual fund investors who have been chosen via convenience sampling technique. It changed into finding that adult males have a high degree of statistics while prominent with females as far as understandings and running of mutual finances. Investors have located significant bias in the cases of cognitive dissonance bias, representative bias, and framing bias regarding the proportion of financial savings invested in mutual funds.